Sales Promotion as a Tool for Improving Customer-Based Brand Equity in Kano Metropolis - Umar, M.J.; Abdulmutallib, U.B. (Kashere Journal of Education, 2022)
Managing and building strong brand is seen today as the main goal of every organization. Having a strong brand is significant important to every organization as it result in having greater customers, achieving competitive advantage and brand extension. However, marketing researchers have not address how strong brand (brand equity) may be managed, built and improved through sales promotions. The study investigated sales promotion as a tool for improving customer-based brand equity by business organizations within Kano metropolis. The paper is conceptual. Therefore, it concludes that sales promotion as a promotional tool has a significant improvement on customer-based brand equity in Kano metropolis. Therefore, to have strength in terms of market leadership and market share, organizations must pay higher attention to their marketing activities such as sales promotion and this can be achieved by improving on the quality and awareness of the brand product and services. It is therefore, recommended that sales promotion should be strengthened and used by the organizations to create and manage strong brand as it have a positive impact on the attribute of brand knowledge which are believed to have an improvement on customer-based brand equity.